Sensing and Degradation of Organophosphorus Compounds by Exploitation of Heat-Loving Enzymes - Giuseppe Manco; Eros A. Lampitella; Nagendra S. K. Achanta; Giuliana Catara; Maria Marone; Elena Porzio (Chemosensors)
The increasing incidence of organophosphate (OP) pesticide poisoning and the use of OP chemical warfare agents (CWA) in conflicts and terrorist acts need sustainable methods for sensing, decontamination, and detoxification of OP compounds. Enzymes can serve as specific, cost-effective biosensors for OPs. We will report on recent advancements in the use of carboxylesterases from the Hormone-Sensitive Lipase for the detection of OP compounds. In addition, enzymatic-based OP detoxification and decontamination offer long-term, environmentally friendly benefits compared to conventional methods such as chemical treatment, incineration, neutralization, and volatilization. Enzymatic detoxification has gained attention as an alternative to traditional OP-detoxification methods. This review provides an overview of the latest research on enzymatic sensing and detoxification of OPs, by exploiting enzymes, isolated from thermophilic/extremophilic Bacteria and Archaea that show exceptional thermal stability and stability in other harsh conditions. Finally, we will make examples of integration between sensing and decontamination systems, including protein engineering to enhance OP-degrading activities and detailed characterization of the best variants.